Clinical presentation and treatment paradigms of brain arteriovenous malformations in patients with hereditary hemorrhagic telangiectasia. (May 2018) - Gamboa, Nicholas T.; Joyce, Evan J.; Eli, Ilyas; Park, Min S.; Taussky, Philipp; Schmidt, Richard H.; McDonald, Jamie; Whitehead, Kevin J.; Kalani, M. Yashar S.
Highlights: We retrospectively identified 39 patients with HHT and single or multiple brain AVMs. The 78 brain AVMs were most commonly found in the supratentorial compartment. Most brain AVMs in our HHT patients were in the bilateral frontal lobes. Most were Spetzler-Martin grades 1 or 2, amenable to surgical resection alone. Almost two thirds of patients had HHT type 1; the rest had HHT type 2. Abstract: Hereditary hemorrhagic telangiectasia (HHT) is characterized by recurrent spontaneous epistaxis, mucocutaneous telangiectases, and multisystem arteriovenous malformations (AVMs). Brain AVMs typically present at birth and are identified in approximately 10–20% of patients with HHT. A retrospective review was undertaken of all HHT patients with known single or multiple brain AVMs treated at our institution. Thirty-nine patients with brain AVM(s) were diagnosed with HHT. Most patients presented with at least one Curaçao criterion. A total of 78 brain AVMs were identified in 39 patients. Two-thirds of patients had solitary brain AVMs, whereas 33% of patients harbored at least two lesions (range: 2–16). Brain AVMs of the supratentorial cerebral hemispheres comprised 83% of all lesions, whereas infratentorial lesions accounted for only 17%. Of the 55 brain AVMs assigned Spetzler-Martin grading, the majority of patients were Grade 1 (73%), and 23% and 4% were Grades 2 and 3, respectively. Patients were treated with surgery alone (51%), embolization alone (6%), embolization followed by surgery (9%), stereotactic radiosurgery (11%), stereotactic radiosurgery followed by surgery (3%), or observation (20%). Of patients who underwent genetic analysis, 62% possessed mutations in ENG (HHT type 1), whereas 38% had mutations in ACVRL1 (HHT type 2). This robust patient cohort of brain AVMs in 39 patients with HHT advances the collective understanding of this disease's varied presentation, diagnostic workup, genetic underpinnings, and available treatment options.